Pendahuluan Menggagas Prototipe Mushaf Al-qur’an Standar Indonesia Riwayat Qalun Menurut Tharîq al-syâthibiyyah - Sofyan Hadi (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
This research was written with the aim of presenting a manuscript of the Al-Qur'an which is easily accessible to the Muslim community in Indonesia in studying and practicing reading the Qur'an from the history of Qalun through the initial step in the form of